PENGARUH INFLASI, PRODUK DOMESTIK BRUTO, SUKU BUNGA DAN KURS USD TERHADAP KREDIT BERMASALAH PADA PT ADIRA DINAMIKA MULTIFINANCE TBK PERIODE 2015-2024 - Azhari Azhari; Anum Nuryani (Journal Economics Technology And Entrepreneur, 2026)
This study examines the impact of non-performing loans at PT Adira Dinamika Multifinance Tbk as influenced by inflation, GDP, interest rates, and the USD exchange rate during the 2015–2024 period. This quantitative research employs descriptive statistics, multiple linear regression, classical assumption tests, hypothesis testing, and the coefficient of determination (R²). The empirical results show that non-performing loans are significantly affected by inflation, as indicated by t-value = -3.917 < 2.57058 and a significance value of 0.011 < 0.05. However, there is no significant partial effect of GDP (t-value = -0.384 < 2.57058; sig. 0.717 > 0.05), interest rates (t-value = -0.350 < 2.57058; sig. 0.741 > 0.05), or the USD exchange rate (t-value = -2.500 < 2.57058; sig. 0.054 > 0.05). Nevertheless, collectively these variables have a significant effect on non-performing loans, with F-value = 7.965 > F-table = 4.74 and a significance level of 0.021 < 0.05. These findings highlight the importance of macroeconomic stability in maintaining financial quality.